(untitled) (KYAMC Journal, 2022)
Background: The whole world is going through a grim crisis instigated by the Novel Coronavirus (COVID-19) pandemic. Health systems of Bangladesh are overburdened in response to the disease. Healthcare workers (HCWs) are at a high risk of getting the infection and the source of transmission in the community. Objectives: This study was designed to explore the real scenario about knowledge, perception and practical behavior about COVID-19 among healthcare professionals of Bangladesh to combat the pandemic during the first outbreak of the COVID-19 pandemic in Bangladesh. Findings of this study might be utilized for the promulgation of policy and program for upcoming days. Materials and Methods: This cross-sectional survey was conducted among the adult Bangladeshi healthcare professionals of purposively selected three type of healthcare facilities- a Tertiary level hospital: Bangabandhu Sheikh Mujib Medical University as well as District hospital and Upazila health Complex from highly infected district Narayangonj and low infected district- Brahmanbaria. A number of 241 HCWs were interviewed using a semi-structured self-administered questionnaire electronically via-email, Facebook Messenger or other social media communication. Result: It is observed that knoledge level is higher among the elder people (age >40 years) than the young people (age <30 years) (10.84±0.48 vs 10.13±1.39, p value is 0.003 at 1% level of confidence). Although there was no significant difference in attitude among them (Attitude score in age >40 years vs <30 years age group was 3.24±0.96 vs 2.96±0.635 with p value is >0.05 at 5% level of significance). Conclusion: To reduce the risk of infection among health care professionals who are not in direct contact with patients. Policy and education should be implemented to convey the importance of possible exposure to the virus. KYAMC Journal. 2022;12(04): 190-195